Perceived Diversity of Complex Environmental Systems: Multidimensional Measurement and Synthetic Indicators - Ugo Gasparino; Barbara Del Corpo; Dino Pinelli (Fondazione Eni Enrico Mattei (FEEM), 2006)
The general attitude towards the sustainable management of environmental resources is evolving towards the implementation of participatory (as opposed to the classical command and control) and, especially at local scale, bottom up (as opposed to the classical top down) approaches. This progress pushes a major interest in the development and application of methodologies able to discover and measure how environmental systems tend to be perceived by the different Stakeholders. Due to the nature of the investigated systems, often too complex to be treated through a classical deterministic approach, as typical for hard physical/mathematical sciences, any measurement has necessarily to be multidimensional. In the present report an approach, more typical of soft social sciences, is presented and applied to the analysis of the sustainable management of water resources in seven Southern and Eastern Mediterranean Watersheds. The methodology is based on the development and analysis (explorative factor analysis, multidimensional scaling) of a questionnaire and is aimed at the discovery and measurement of a latent multidimensional underlying structure (conceptual map). It is the opinion of the authors, that the identification of a set of consistent, independent, bottom up and shared synthetic indicators (aggregated indices) could be strongly facilitated by the interpretation of the dimensions of the emerging underlying structure.
Keywords: C13; C42; D74; Q01; Q25; 330; Participative Approach; Cognitive Map; Factor Analysis; Indicators of Sustainability; Sustainable Water; Management